Quantum Dialogue Protocols: A Review - Chauhan , S.; Ahmed, G.; Gupta, N. L. (Journal of Scientific Research, 2022)
In recent years, quantum cryptography (QC) has received much attention in academic and commercial fields. It has proved to be a promising technology for ensuring the security of future data transmission. In this paper, we review the development of a remarkable area of quantum cryptography, i.e., Quantum dialogue (QD), which is currently in the theoretical stage but is of great interest to academics. We will discuss the quantum dialogue protocols in two categories, single photon-based protocols, and entanglement-based protocols, depending on the quantum resource employed. Finally, experimental implementation, comparison and analysis, security and practical feasibility, and future work for the above-mentioned branch will also be discussed.